2013
DOI: 10.1038/gim.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, legal, and social implications of incorporating genomic information into electronic health records

Abstract: The inclusion of genomic data in the electronic health record raises important ethical, legal, and social issues. In this article, we highlight these challenges and discuss potential solutions. We provide a brief background on the current state of electronic health records in the context of genomic medicine, discuss the importance of equitable access to genome-enabled electronic health records, and consider the potential use of electronic health records for improving genomic literacy in patients and providers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 69 publications
0
71
0
Order By: Relevance
“…Finally, the duties of the laboratory in informing HCPs and patients about new findings or conclusions were discussed in nine recent articles, of which five were about a duty to recontact in light of WGS. 33,51,55,58,61 Laboratory staff were thought to have a particular duty to keep physicians and counselors up to date on changes in test interpretations so that information could be appropriately offered to patients. Shirts and Parker 33 discussed the duty of the laboratory directly to the patient in light of direct-to-consumer testing, for which there is no intervening HCP.…”
Section: Recontact In Clinical Genetics: Duty or Not?mentioning
confidence: 99%
“…Finally, the duties of the laboratory in informing HCPs and patients about new findings or conclusions were discussed in nine recent articles, of which five were about a duty to recontact in light of WGS. 33,51,55,58,61 Laboratory staff were thought to have a particular duty to keep physicians and counselors up to date on changes in test interpretations so that information could be appropriately offered to patients. Shirts and Parker 33 discussed the duty of the laboratory directly to the patient in light of direct-to-consumer testing, for which there is no intervening HCP.…”
Section: Recontact In Clinical Genetics: Duty or Not?mentioning
confidence: 99%
“…Genetic test results are considered particularly sensitive, especially from a privacy standpoint [7]. Genetic testing results can be upsetting or life changing, as in the case of Huntington's disease, breast cancer, or a serious congenital condition.…”
Section: Access To Genetic Testing and Hiv Testing Resultsmentioning
confidence: 99%
“…Due to the complexity of the information and social and familial implications, additional delay in releasing results to an electronic portal could be justified based on the time it takes for physicians and genetic counselors to coordinate appropriate follow-up appointments. As there is a shortage of genetic counselors nationwide, some have suggested that genomic medicine tools be developed for the patient portals to allow patients to better understand their results without long waits for appointments with genetic counselors [7].…”
Section: Access To Genetic Testing and Hiv Testing Resultsmentioning
confidence: 99%
“…Likewise some patients may have a strong desire to hold such data, such as those with rare conditions or participants in bio-banking projects who may wish to be closer to their records. However the potential for such data to be lost or misused also generates a higher order of risk than other sorts of medical information, not only to the confidentiality of the patients but also to their families and future generations for whom the sorts of inferences that can be made from genetic data may have damaging social consequences, and thus the ethical, social and legal implications of such innovations will need to be thoroughly researched in order to demonstrate their acceptability [13].…”
mentioning
confidence: 98%